Combination of a Flipped Classroom Format and a Virtual Patient Case to Enhance Active Learning in a Required Therapeutics Course - Lichvar, Alicia Beth (Am J Pharm Educ, 2016)
Objective. To design and evaluate the integration of a virtual patient activity in a required therapeutics course already using a flipped-classroom teaching format. Design. A narrative-branched, dynamic virtual-patient case was designed to replace the static written cases that students worked through during the class, which was dedicated to teaching the complications of liver disease. Students completed pre- and posttests before and after completing the virtual patient case. Examination scores were compared to those in the previous year. Assessment. Students’ posttest scores were higher compared to pretest scores (33% vs 50%). Overall median examination scores were higher compared to the historical control group (70% vs 80%), as well as scores on questions assessing higher-level learning (67% vs 83%). A majority of students (68%) felt the virtual patient helped them apply knowledge gained in the pre-class video lecture. Students preferred this strategy to usual in-class activities (33%) or indicated it was of equal value (37%). Conclusion. The combination of a pre-class video lecture with an in-class virtual patient case is an effective active-learning strategy.